2020
DOI: 10.1105/tpc.20.00280
|View full text |Cite
|
Sign up to set email alerts
|

Synergy among Exocyst and SNARE Interactions Identifies a Functional Hierarchy in Secretion during Vegetative Growth

Abstract: Vesicle exocytosis underpins signaling and development in plants and is vital for cell expansion. Vesicle tethering and fusion are thought to occur sequentially, with tethering mediated by the exocyst and fusion driven by assembly of soluble NSF attachment protein receptor (SNARE) proteins from the vesicle membrane (R-SNAREs or vesicle-associated membrane proteins [VAMPs]) and the target membrane (Q-SNAREs). Interactions between exocyst and SNARE protein complexes are known, but their functional consequences r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 66 publications
1
12
0
1
Order By: Relevance
“…Is the plant exocyst a hot spot of small-GTPase regulation and are interactions between RHO/ROP and RAB GTPases and exocyst only indirect, mediated by adaptors, as reported to date [81,97,98], or could they also be direct as in opisthokonts? Are there more possible PM landmarking proteins targeting exocyst to specific domains and which exocyst subunits/versions interact with SNARE proteins [99]? Is there a more general direct cross-talk between plant exocyst and the cytoskeleton as indicated by the interaction with microtubules in the localization of CESA complexes during xylem CW modification [22,23] and the recently reported binding of exocyst to actin and myosin [100,101]?…”
Section: Plant Exocyst Complex In Defense Against Pathogens and In Sy...mentioning
confidence: 99%
“…Is the plant exocyst a hot spot of small-GTPase regulation and are interactions between RHO/ROP and RAB GTPases and exocyst only indirect, mediated by adaptors, as reported to date [81,97,98], or could they also be direct as in opisthokonts? Are there more possible PM landmarking proteins targeting exocyst to specific domains and which exocyst subunits/versions interact with SNARE proteins [99]? Is there a more general direct cross-talk between plant exocyst and the cytoskeleton as indicated by the interaction with microtubules in the localization of CESA complexes during xylem CW modification [22,23] and the recently reported binding of exocyst to actin and myosin [100,101]?…”
Section: Plant Exocyst Complex In Defense Against Pathogens and In Sy...mentioning
confidence: 99%
“…Deregulated secretory processes in mlo and exo70 mutants may result in a constitutively altered cell wall architecture in these mutants, which might in part account for their altered pathogen infection phenotypes. Recently reported direct interactions of both MLOs and plant exocyst subunits (including EXO70s) with SNARE proteins reinforce the conclusion that both types of proteins are part of a hierarchical module regulating exocytosis (Meng et al, 2020;Ortmannová et al, 2022;Larson et al, 2020). Although we consider the PMR4 callose synthase as an important cargo of EXO70-MLO cooperation in the context of trichome secondary cell walls, PMR4 is unlikely to play a major role regarding powdery mildew resistance as a previous study demonstrated that mlo2-mediated resistance is independent of PMR4-based callose deposition (Consonni et al, 2010).…”
Section: Our Studies Demonstrated Physical Interactions Between Exo70...mentioning
confidence: 85%
“…The exocyst complex, consisting of SEC3, SEC5, SEC6, SEC8, SEC15, Exocyst 70 (EXO70) and EXO84, tethers a secretory vesicle to the PM, which is regulated by small GTPases (Hong & Lev, 2014). EXO70A1 interacts with SYP121, SNAP33 and VAMP721/722 (Larson et al ., 2020). In the exo70A1 mutant, the PM localization of SYP121 and VAMP721/722 was reduced, resulting in impairing the SYP121‐dependent secretion.…”
Section: Regulation Of Immune Exocytosismentioning
confidence: 99%